2021
DOI: 10.3390/math9121417
|View full text |Cite
|
Sign up to set email alerts
|

A Knowledge-Based Hybrid Approach on Particle Swarm Optimization Using Hidden Markov Models

Abstract: Bio-inspired computing is an engaging area of artificial intelligence which studies how natural phenomena provide a rich source of inspiration in the design of smart procedures able to become powerful algorithms. Many of these procedures have been successfully used in classification, prediction, and optimization problems. Swarm intelligence methods are a kind of bio-inspired algorithm that have been shown to be impressive optimization solvers for a long time. However, for these algorithms to reach their maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 106 publications
0
1
0
Order By: Relevance
“…Within the literature, recent studies can be found that use hybrid algorithms that solve the coverage problem [5,[48][49][50]. However, to compare a hybrid algorithm that resembles our proposal, we have considered making a comparison of results with hybrid algorithms that work with bio-inspired metaheuristics, improved by ML, and they solve the set covering problem.…”
Section: Comparison Results In Similar Hybrid Algorithmsmentioning
confidence: 99%
“…Within the literature, recent studies can be found that use hybrid algorithms that solve the coverage problem [5,[48][49][50]. However, to compare a hybrid algorithm that resembles our proposal, we have considered making a comparison of results with hybrid algorithms that work with bio-inspired metaheuristics, improved by ML, and they solve the set covering problem.…”
Section: Comparison Results In Similar Hybrid Algorithmsmentioning
confidence: 99%
“…Paper [8] deals with particle swarm optimization. For bio-inspired algorithms, where a proper setting of the initial parameters by an expert is required.…”
mentioning
confidence: 99%